A number theory problem by Mateus Gomes

For n = 10 n=10 , find the remainder of 3 2 n 1 3^{2^n} - 1 when it is divided by 2 n + 3 2^{n+3} .


The answer is 4096.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Kushal Bose
Nov 10, 2016

Putting n = 10 n=10

3 2 10 1 = ( 3 2 9 + 1 ) ( 3 2 9 1 ) = ( 3 2 9 + 1 ) ( 3 2 8 + 1 ) ( 3 2 8 1 ) = = ( 3 2 9 + 1 ) ( 3 2 8 + 1 ) ( 3 2 8 1 ) . . . ( 3 2 2 + 1 ) ( 3 2 + 1 ) ( 3 + 1 ) ( 3 1 ) 3^{2^{10}}-1=(3^{2^9}+1)(3^{2^9}-1)\\ =(3^{2^9}+1)(3^{2^8}+1)(3^{2^8}-1) \\ = \cdots \\ =(3^{2^9}+1)(3^{2^8}+1)(3^{2^8}-1)...(3^{2^2}+1)(3^{2}+1)(3+1)(3-1)

Each of the 12 factors will release exactly a single factor of 2 because in the binomial expansion of 3 2 k + 1 3^{2 k}+1 will give a factor 2 and rest part is odd.

So the number will be 3 2 10 1 = 2 12 ( 2 m + 1 ) = 2 12 . 2 m + 2 12 = 2 13 m + 2 12 3^{2^{10}}-1=2^{12}(2 m+1) \\ =2^{12}.2m +2^{12} \\ =2^{13}m + 2^{12}

So the remainder is 2 12 = 4096 2^{12}=4096

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...